Effects of climate change on irrigation adoption in Brazil - Dênis Antônio da Cunha; Alexandre Bragança Coelho; José Gustavo Féres; Marcelo José Braga (Acta Scientiarum. Agronomy, 2014)
http://dx.doi.org/10.4025/actasciagron.v36i1.15375The aim of this paper is to analyse the effects of climate change on irrigation adoption in Brazil. Temperature and precipitation projections for the 2010-2099 periods were employed under a number of different climate scenarios according the 4th Assessment Report of Intergovernmental Panel on Climate Change (IPCC). The results show that irrigation adoption will be affected by climate change. Given current conditions, irrigation has generally been adopted in Brazil to cope with reduced precipitation and temperature variations. The estimated irrigation probabilities in the future scenarios were quite different across Brazilian regions. The main explanation for this pattern is the distinct climatic conditions and production structures. Considering future climate change, over the next 30 years (2010 to 2039), the irrigation probability is expected to increase in all Brazilian regions. However, this trend is reversed in the long run.